Botswana : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper for Botswana highlights the macroeconomic impact of an effectively implemented National Strategic Framework (NSF) program. The NSF is anchored on the goals of prevention, care, and support; management of the national response; economic impact mitigation; and provision of a strengthened legal and ethical environment. The treatment of the pandemic focuses on the administration of antiretroviral drugs to the infected, the effect of which would be to prolong their lifespan, as well as increase the average level of productivity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet